Reinterpretasi Konsep Halalan Thayyiban dalam Q. S. Al-Baqarah Ayat 168: Analisis Kontekstual Abdullah Saeed terhadap Sertifikasi Halal BPJPH - Sari, Aisi Nurmala (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
The research in this article is to analyze the correlation between the concept of halalan thayyiban in Q.S. al-Baqarah: 168 related to halal certification decided by BPJPH. Seeing in this contemporary era, the standardization of halalan thayyiban in food and beverages has not been given much attention by the public as consumers and companies as producers. For example, there are still various types of products circulating in the scope of society that are not guaranteed halal. This research uses a descriptive-analytical method in the form of a contextual theory analysis knife by Abdullah Saeed. Abdullah Saeed’s theory is used because the purpose of this research is not enough just to find the relationship but also to see how useful it is and its impact on society in general. The result of this study state that the requirements related to halal products determined by BPJPH find a fairly comprehensive level of correlation with Q.S. al-Baqarah: 168. However, in reality, the current level of public awareness of product halalness is still low. But on the other hand, it also has many positive impacts on the general public because the concept of halal in Islam is not just halal, but also includes those that are hygienic, clean, healthy and useful. So that the legal provisions related to halal products can be accepted by various groups, both Muslims themselves and non-Muslims, because they provide many benefits.